Strategi Pemasaran Terhadap Kualitas Pelayanan dan Kepuasan Pasien di Puskesmas Tambak Rejo Kota Surabaya - Megatama, Abitri Wahyuni; Tjokro, Silvia Haniwijaya; Geonarso, Roberto; Putri, Linta Meyla (Bagian Penelitian & Pengabdian Masyarakat STIKES Adi Husada, 2024)
Background: Understanding the needs and desires of consumers, in this case patients, is an important thing that affects the quality of service for patients. Satisfied patients are a very valuable asset because if patients are satisfied they will continue to use the services of their choice, but if patients feel dissatisfied they will tell other people twice as much about their bad experience.Purpose: This study aims to determine the effect of visits on marketing and patient satisfaction at the Tambak Rejo Health Center.Aims: This study aims to determine the effect of visits on marketing and patient satisfaction at the Tambak Rejo Health Center.Methods: The design used in this research is quantitative. type of research that is systematic, planned, structured, uses lots of numbers starting from data collection, processing to results and emphasizes objective phenomena and is studied quantitatively. The research variables consist of: level of satisfaction and patient visits (dependent) and service quality (independent). Questionnaires on the level of patient satisfaction and visits and service quality used instruments that had been developed by the Tambak Rejo Health Center.Results: The results of the study showed that patients who visited used BPJS Mandiri, BPJS PBI, Mandiri with a level of satisfaction including compliance with requirements of 61.3%, ease of service procedures 64.2%, fairness of costs 71.2% and quality of facilities and infrastructure 77.8%. The quality of infrastructure can increase the number of patient visits, namely ≤ 1500 visits.Conclusion: The Tambak Rejo Health Center excels in marketing strategy, service quality and patient satisfaction. By prioritizing aspects of the Puskesmas, Puskemas provides easily accessible and quality health services that are aligned with the needs and expectations of patients